Oracle SOA suite developer's guide : design and build service-oriented architecture solutions with the Oracle SOA Suite 10gR3 - Wright, Matt, 1980-; Reynolds, Antony (Packt Pub., 2009)
"We are moving towards a standards-based Service-Oriented Architecture (SOA), where IT infrastructure is continuously adapted to keep up with the pace of business change. Oracle is at the forefront of this vision, with the Oracle SOA Suite providing the most comprehensive, proven, and integrated tool kit for building SOA based applications"--Resource description page
Title from title screen.
Keywords: Oracle (Computer file); Relational databases.; Web services.; Service-oriented architecture (Computer science); Computer network architectures.; Information resources management.; elektronické knihy; electronic books